Effects of dietary omega-3 fatty acids on bones of healthy mice. Issue 5 (October 2019) - Anez-Bustillos, Lorenzo; Cowan, Eileen; Cubria, Maria B.; Villa-Camacho, Juan C.; Mohamadi, Amin; Dao, Duy T.; Pan, Amy; Fell, Gillian L.; Baker, Meredith A.; Nandivada, Prathima; Nazarian, Ara; Puder, Mark
Summary: Background & aims: Altering the lipid component in diets may affect the incidence of metabolic bone disease in patients dependent on parenteral nutrition. Consumption of polyunsaturated fatty acids (PUFA) can impact bone health by modulating calcium metabolism, prostaglandin synthesis, lipid oxidation, osteoblast formation, and osteoclastogenesis. The aim of this study was to evaluate the dietary effects of PUFA on murine bone health. Methods: Three-weeks-old male (n = 30) and female (n = 30) C57BL/6J mice were randomized into one of three dietary groups. The diets differed only in fat composition: soybean oil (SOY), rich in ω-6 PUFA; docosahexaenoic acid alone (DHA), an ω-3 PUFA; and DHA with arachidonic acid, an ω-6 PUFA, at a 20:1 ratio (DHA/ARA). After 9 weeks of dietary treatment, femurs were harvested for micro-computed tomographic analysis and mechanical testing via 3-point bending. Separate mice from each group were used solely for serial blood draws for measurement of biomarkers of bone formation and resorption. Results: At the microstructural level, although some parameters in cortical bone reached differences that were statistically significant in female mice, these were too small to be considered biologically relevant. Similarly, trabecular bone parameters in male mice were statistically different in some dietary groups, although the biological interpretation of such subtle changes translate into a lack of effect in favor of any of the experimental diets. No differences were noted at the mechanical level and in blood-based biomarkers of bone metabolism across dietary groups within gender. Conclusions: Subtle differences were noted at the bones' microstructural level, however these are likely the result of random effects that do not translate into changes that are biologically relevant. Similarly, differences were not seen at the mechanical level, nor were they reflected in blood-based biomarkers of bone metabolism. Altogether, dietary consumption of PUFA do not seem to affect bone structure or metabolism in a healthy model of growing mice.